2011
DOI: 10.2139/ssrn.1710882
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Mental Health Courts

Abstract: To date, no scholarly article has analyzed the theoretical basis of mental health courts, which currently exist in forty-three states. This Article examines the two utilitarian justifications proposed by mental health court advocates-therapeutic jurisprudence and therapeutic rehabilitation-and finds both insufficient. Therapeutic jurisprudence is inadequate to justify mental health courts because of its inability, by definition, to resolve significant normative conflict. In essence, mental health courts expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Treatment courts are based on the assumption that certain criminal behaviors are rooted in disorders that make offenders less blameworthy. These carry with them the implication that certain individuals lack autonomy—that is, that their criminal behavior is not totally within their control—yet they still deserve the stigma that comes with being in the criminal justice system (Johnston ). Mental health courts, for example, are predicated on the belief that some criminal behavior is based on mental health disorders and that both punishing through sanctions and treating the underlying mental health disorder will prevent recidivism (Bernstein and Seltzer ; Perez, Leifman, and Estrada ).…”
Section: Vtcs As Part Of the Therapeutic Jurisprudence Movementmentioning
confidence: 99%
“…Treatment courts are based on the assumption that certain criminal behaviors are rooted in disorders that make offenders less blameworthy. These carry with them the implication that certain individuals lack autonomy—that is, that their criminal behavior is not totally within their control—yet they still deserve the stigma that comes with being in the criminal justice system (Johnston ). Mental health courts, for example, are predicated on the belief that some criminal behavior is based on mental health disorders and that both punishing through sanctions and treating the underlying mental health disorder will prevent recidivism (Bernstein and Seltzer ; Perez, Leifman, and Estrada ).…”
Section: Vtcs As Part Of the Therapeutic Jurisprudence Movementmentioning
confidence: 99%
“…A study by Vieira, Skilling, and Peterson-Badali (2009) showed that the more individual needs were matched to services, the lower the recidivism for delinquent youth. Even though the relationship between mental illness and criminal behavior is debatable (see Johnston 2012), Barrett et al (2014) found a relationship between a range of mental health disorders and delinquency in a matched case-control study. Furthermore, even if mental health problems were not a direct causal factor for a youth’s involvement in delinquent behavior, addressing mental health needs along with other needs may be necessary to foster healthy development, leading to a range of improved outcomes, including delinquent-type problem behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the statute under which this court was established states that the prosecutor can divert cases, “when mental illness contributed to the crime,” it does not give guidance as to what factors should be used in making this determination (Indiana Code 12-23-5-1). Guides for designing MHCs are equally silent, treating the question of guilt or the extent to which culpability might be mitigated by mental illness as unproblematic (Johnston, 2012). Yet such determinations bring us directly to the question of who deserves the special treatment of MHC (Draine et al, 2007; Johnston, 2012; Wolff, 2003).…”
Section: Discussionmentioning
confidence: 99%